Grammatical metaphor in academic texts of Indonesian students’ thesis - Mahmudah; Hajrah; Arni Amir; Muhammad Ahkam Arifin (Center for Humanities and Innovation Studies, 2018)
The purpose of this research is to reveal the form and pattern of lexical shift either lexically or grammatically by (1) to describe the form of grammatical metaphor of academic text, and (2) to describe the pattern of lexical shift in academic texts. The type of this research is qualitative research using Functional Systemic Linguistic approach. The academic texts was analyzed using theory of M.A.K. Halliday. The data in this study are words, phrases, clauses, and sentences in academic texts that undergo lexical and sentence shifts. The data source in this research is thesis of Indonesian Language and Literature Study Program in the year of 2015. Data collection techniques are documentation, reading, and record technique. The results found forms of grammatical metaphor which include (1) nominalization, (2) groups of nouns, and (3) simplex phrases. The lexic shift patterns found in this study include: (1) verbs to nouns, (2) adjectives to nouns, (3) adverbs to nouns, and (4) nouns to nouns.